PELATIHAN BIMBINGAN PROFETIK BERBASIS METODE SOKRATIK UNTUK MENINGKATKAN KESIAPAN PERNIKAHAN DAN MENGHINDARI STUNTING PADA REMAJA - Santosa, Hardi; Ahmad Ahid Mudayana; Iin Inawati; Akhmad Fajar Prasetya; Siti Partini (Fakultas Pertanian, 2025)
The main problem faced by adolescents in the place of community service is the challenge of maintaining chastity and low knowledge of marriage preparation and stunting. The advancement of information technology which also has implications for the rise of pornography, is a serious problem that must be faced by adolescents today. Not to mention the understanding of child free which every year continues to increase into a big monster and is quite frightening for the development of a healthy young generation in facing the nature of family life. Partners in this PkM activity are teenagers in the Youth Organization community in Caturharjo Village. This community service aims to increase understanding of marriage readiness and stunting-free to successfully build a household in the future. To achieve the goal, training based on the socratic method was used. The socratic method functions to organize the minds of adolescents more systematically and comprehensively through reflective thinking to avoid misconceptions. The success of the service is measured by the results of the pre-test and post-test. The results of the service show that there is an average increase of 21 points, this shows that the training is effective.